STUDY OF CORRUPTION IN THE PERSPECTIVE OF DIGNIFIED JUSTICE - YB Irpan (Surakarta Law and Society Journal, 2019)
Criminal acts of corruption are transnational in nature, adversely affecting the life of the nation and state. The loss of state finances reached hundreds of trillions of rupiah, people's trust in the authorities decreased, economic costs became high, important government projects were abandoned, the cost of higher education was not affordable anymore by ordinary people, so that corruption was called extraordinary crime and therefore the handling of acts criminal corruption must be special. The return of state financial losses due to corruption is very important. The existence of state financial losses must be returned by corruptors because corruption is an act that violates human values. Recovering state financial losses can not only be done through court procedures but can also be done through out-of-court channels. Increasing the strong will of the government, law enforcement and the public in combating corruption in this country indiscriminately so that the recovery of state financial losses can be effective so as to be able to realize a dignified Indonesian nation. Keywords: Accountability, Corruption; Dignified Justice.